A Madame Bovary for a New Millennium: Leïla Slimani’s Dans le jardin de l’ogre (2014) - Christiansen, Hope (Dalhousie French Studies)

(untitled) (Department of French, Dalhousie University, 2022)
Best known for her 2016 suspense novel, Chanson douce, Leïla Slimani first attracted attention for her novel about a female sex addict, Dans le jardin de l’ogre. Having realized that women never figure in media accounts of sexual addiction, she immersed herself in Leo Tolstoy’s Anna Karenina, François Mauriac’s Thérèse Desqueyroux, Joseph Kessel’s Belle de jour, and Gustave Flaubert’s Madame Bovary. Reviewers of Dans le jardin de l’ogre often mention the latter in passing, and Slimani herself has identified Emma as one of her favorite heroines, but thus far there has been only one scholarly study that deals with specific connections between the two novels. While they seem unlikely bedfellows on the surface—Flaubert’s text is a traditional nineteenth-century roman de formation that unfolds in linear fashion, while Slimani’s is decidedly modern in subject and in its slippage back and forth in time—a close reading reveals numerous uncanny similarities in narrative technique, characterization, themes, and motifs. It is hard to imagine a more promising pairing to test Julia Kristeva’s theory that “tout texte se construit comme mosaïque de citations, tout texte est absorption et transformation d’un autre texte” (85). This study shows that Dans le jardin de l’ogre is one of those mosaics that has “absorbed” many of Madame Bovary’s salient features and “transformed” them into something quite modern and distinctive.